2006 SICE-ICASE International Joint Conference 2006
DOI: 10.1109/sice.2006.315532
|View full text |Cite
|
Sign up to set email alerts
|

Development and Control of an Autonomously Obstacle-Navigation Inspection Robot for Extra-High Voltage Power Transmission Lines

Abstract: This paper presents a mobile robot suspended on power transmission lines based on a novel movement mechanism with two manipulators and a body. After the inspection robot configuration is described, the kinematics of the inspection robot and the process of obstacle-navigation are analyzed in details. In order to achieve autonomously control the task-oriented integrated control architecture is adopted, and the architecture is a multi-agent system coordinate and organized by distribute blackboard. To achieve auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 8 publications
(12 reference statements)
0
23
0
1
Order By: Relevance
“…Not having proper shielding and mechanisms for overcoming obstacles, the proposed robot could not travel on phase conductors. A more complex robot mechanism, presented in (Tang et al, 2004), had two arms (front arm and rear arm) and a body. Each arm had 4 degrees of freedom and a gripper with a running wheel.…”
Section: Robot Mechanisms and Obstacle Traversingmentioning
confidence: 99%
See 1 more Smart Citation
“…Not having proper shielding and mechanisms for overcoming obstacles, the proposed robot could not travel on phase conductors. A more complex robot mechanism, presented in (Tang et al, 2004), had two arms (front arm and rear arm) and a body. Each arm had 4 degrees of freedom and a gripper with a running wheel.…”
Section: Robot Mechanisms and Obstacle Traversingmentioning
confidence: 99%
“…One of the first robot control algorithms for power line inspection was described in (Sawada et al, 1991). A more complex control system, using a distributed expert system that was divided between the robot and the ground station, was described in (Tang et al, 2004). The robot control system would run on an embedded PC/104 based computer, connected to the ground station with a wireless data link and a separate image transmission channel.…”
Section: Robot Control Systemmentioning
confidence: 99%
“…One of these mechanisms has been shown in Figure 13. This figure shows a sketch of the mechanical mechanism designed by (Tang et al, 2004). The proposed robot has two front and rear arms and a body.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…14. Proposed obstacle navigation procedure in (Tang et al, 2004) The obstacle navigation process is shown in Figure 14. When the robot detects an obstacle, the rear arm gripper grasps the line, and the front arm elongates to pass the obstruction.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…In order to assist and obtain a stable motion in the single-supported phase it is important to either anchor the supporting arm to the line with gripper to resist the gravity or control the total center of gravity position beneath the supporting arm. A dual-arm robot designed for live-line inspection of extra-high-voltage is presented in [8], this platform is designed to hang from the OGW on its two wheeled arms, the control box containing electrical and electronic components can be shifted forward or backward to center the mass on either of the two arms, by which the robot is hanging to keep the horizon pose of the body and protect the line against the gripping forces. Due to additional counter-weight system, obstacle-navigation process of this robot is complex and time-consuming.…”
Section: Introductionmentioning
confidence: 99%